Residual Activatability of Circulating Tfh17 Predicts Humoral Response to Thymodependent Antigens in Patients on Therapeutic Immunosuppression - Dahdal, Suzan; Saison, Carole; Valette, Martine; Bachy, Emmanuel; Pallet, Nicolas; Lina, Bruno; Koenig, Alice; Monneret, Guillaume; Defrance, Thierry; Morelon, Emmanuel; Thaunat, Olivier (Frontiers in Immunology, 2019)
The generation of antibodies against protein antigens (such as donor-specific HLA molecules) requires that T follicular helper cells (Tfh) provide help to B cells. Immunosuppressive (IS) armamentarium prevents T cell activation, yet a significant proportion of renal transplant patients develop donor-specific antibodies (DSA), which suggests that IS drugs do not efficiently block their T follicular helper cells. To test this hypothesis, the number of circulating Tfh, their polarisation profile, and ability to up-regulate i) the costimulatory molecules CD40L and ICOS, and ii) the activation marker CD25, following in vitro stimulation in presence of IS drugs, were compared between 36 renal transplant patients (6-72 months post transplantation) and 9 healthy controls. IS drugs reduced the number of Tfh1 and 2 but had little impact on Tfh17, which was the dominant subset in transplant patients. Although IS drugs decreased activation-induced expression of costimulatory molecules by Tfh, the impact was highly variable between individuals. Furthermore, 20% of transplant patients displayed normal expression of CD25 on Tfh following in vitro stimulation (i.e. "residual activatability"). To test whether residual activatability of Tfh correlates with antibody response against thymo-dependent antigens we took advantage of the 2015 influenza vaccination campaign, which provided a normalized setting for antigenic stimulation. In line with our hypothesis, responders to influenza vaccine exhibited significantly higher percentage of CD25-expressing Tfh17 after in vitro stimulation. A results that was confirmed retrospectively in 9 transplanted patients at the time of first DSA detection. We concluded that "residual activatability" of Tfh17 might be used as a non-invasive biomarker to identify transplant patients at higher risk to develop DSA under immunosuppression. If validated in larger studies, this assay might help optimising the prevention of DSA through personalised adaptation of immunosuppressive regimen.